Impact of controlled-release urea on rice yield, nitrogen use efficiency and soil fertility in a single rice cropping system - Chen, Zhaoming; Wang, Qiang; Ma, Junwei; Zou, Ping; Jiang, Lina (Scientific reports, 2020)
Overuse of nitrogen (N) fertilizer has led to low N use efficiency (NUE) and high N loss in single rice cropping systems in southeast China. Application of controlled-release urea (CRU) is considered as an effective N fertilizer practice for improving crop yields and NUE. Here, field experiments were conducted during 2015–2017 to assess the effects of two CRUs (resin-coated urea (RCU) and polyurethane-coated urea (PCU)) on rice yields, NUE and soil fertility at two sites (Lincheng town (LC) and Xintang town (XT)). Four treatments were established at each site: (1) control with no N application (CK), (2) split application of conventional urea (U, 270 kg N ha −1 ), (3) single basal application of RCU (RCU, 216 kg N ha −1 ), and (4) single basal application of PCU (PCU, 216 kg N ha −1 ). The N application rate in the CRU treatment compared to the U treatment was reduced by 20%. However, the results showed that, compared to split application of urea, single basal application of CRU led to similar rice grain yields and aboveground biomass at both sites. No significant difference in the N uptake by rice plant was observed between the U and CRU treatments at either site. There were no significant differences in the N apparent recovery efficiency (NARE) among the U, RCU and PCU treatments, with the exception of that in XT in 2015. Compared to application of U, application of CRU increased the N agronomic efficiency (NAE) and N partial factor productivity (NPFP) by 17.4–52.6% and 23.4–29.8% at the LC site, and 15.0–84.1% and 23.2–33.4% at the XT site, respectively, during 2015–2017. Yield component analysis revealed that greater rice grain yield in response to N fertilizer was attributed mainly to the number of panicles per m 2 , which increased in the fertilized treatments compared to the CK treatment. The application of CRU did not affect the soil fertility after rice harvest in 2016. Overall, these results suggest that single basal application of CRU constitutes a promising alternative N management practice for reducing N application rates, time- and labor-consuming in rice production in southeast China.